The Islamic laws of wills as applied in Malaysia / Mohd Shahrom Mohamad - Mohamad, Mohd Shahrom (Faculty of Law, 1982)
The Islamic Law on wills is an important area of law which has often been the subject of misinterpretation. This is so because muslims themselves tend to take things for granted and when making bequests, no advice is sought and even where advice is given, it may happen that the will still does not comply with the requirements of Islamic Law.As such I feel that before dicussing the application of the Islamic Law of wills in Malaysia, it is irnportan.t to lay down the main principles and requirements of the law. In the first chapter of this paper I have discussed the principles by sub-dividing the various requirernents as seen from the general point of view